Love Money, Ethical Perception And Earning Management Behavior for Lecturer - Wany, Eva; Narsa, I Made; Basuki (CENTRAL ASIA AND THE CAUCASUS, 2021)
This study aims to examine the influence of the behavior of love money and the perception of ethical behavior on perceptions of earning management, using participants, the academics who followed workshop activities from all over Indonesia. This study focused on love money and ethics perception influences earning management perception. This experimental research design used 2x2 between- subjects to investigate participants who are the lecturers from Indonesia. The method of analysis used regression analysis. The results indicated that there is an influence of attitude of love money and perception of ethics on the behavior of earnings management.